A systematic review and synthesis of research and practice : linking an organisation’s strategic planning with a national vision for a sustainable future : the case of FNB Namibia - Louw, Nina (Stellenbosch : Stellenbosch University, 2016)
Thesis (MComm)—Stellenbosch University, 2016.